The Denotation and Connotation in The Songs Entitled “Exile”, “Illicit Affair” U, and “Cardigan” by Taylor Swift - Mashuri Mashuri; Arif Hidayat; Nadhilah Fauziah (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This research discussed about the denotation and connotation in selected songs of Taylor Swift album entitled Folklore. The researcher applied descriptive qualitative methodology by using the semiotic theory of Ferdinand de Saussure and structuralism by Claude Levi Strauss. The data source of this study is Taylor Swift selected songs. Those songs are “Exile”, “Illicit Affair”, and “Cardigan”. The result of this research shows that there are implicit meaning in the lyrics of the songs. (1) There are the denotation meaning in selected songs. (2) There are the connotative meaning in the selected songs. (3) There are the myth showed in the selected songs. Taylor Swift connected the songs in this album one to another.